Passing of Mr. John Paulo D. Asong - Asong, John Paulo D. (Animo Repository, 2022)
CCHRSO announced to the Lasallian community with sadness passing of Mr. John Paulo "Throi" D. Asong, Executive Assistant of the Tañada-Diokno College of Law.